Synthesis, characterization and biological activities of Ag(I) complexes with mixed thiazolidine and mono-, BI-dentate phosphine ligands / Nur Rahimah Fitrah Mohd Sofyan - Nur Rahimah Fitrah , Mohd Sofyan (2018)
Five silver(I) complexes containing mixed ligand system of phosphine and thiazolidine were successfully synthesized. The structural information of the complexes was assembled using various spectroscopic techniques such as CHN elemental analysis, Fourier Transformed Infrared (FTIR) spectroscopy, 1H, 13C, and 31P{1H} NMR spectroscopy and thermogravimetric analysis (TGA). A bindetate phosphine ligand acted as chelating agent which bond to the Ag in 1:2 molar ratios. Meanwhile, thiazolidine was attached to the Ag in a 1:1 molar ratio. The antiplasmodial properties of all synthesized complexes were investigated on chloroquine resistant P. falciparum parasite via HRP2 assays and cytotoxicity tests on MDBK cells. Of all the synthesized complexes, complex 2 showed the highest SI value (˃ 12.279) followed by complex 5 (5.218). The potent properties of compounds 2 and 5 were also noted in the in vitro antiproliferative assays involving MDA-MB-231 and MCF-7 breast cancer cell lines as well as HT-29 colon cancer cell line. Complex 2 was selective for MDA-MB-231 cells (GI50 = 1.957 ± 0.347 μM), while complex 5 acted predominantly on breast carcinoma cells (GI50 MDA-MB-231 = 9.328 ± 2.162 μM; MCF-7 = 5.784 ± 1.821 μM) instead of colon carcinoma (HT29) cells (GI50 = 30.220 ± 3.744 μM).